Drug Interactions with Gender-Affirming Hormone Therapy: Focus on Antiretrovirals and Direct Acting Antivirals. (2nd July 2020) - Cirrincione, Lauren R.; Senneker, Tessa; Scarsi, Kimberly K.; Tseng, Alice
ABSTRACT: Introduction: Gender-affirming care may include hormonal therapy to attain desired health outcomes in transgender (trans) individuals. To provide safe, affirming medical care for trans patients, health care providers must identify and manage drug-drug interactions (DDIs) between gender affirming hormonal therapy (GAHT) and other medication therapies. Areas covered: This review summarizes available data on DDIs between GAHT and antiretrovirals (ARVs) or hepatitis C direct acting antivirals (DAAs). Potential pharmacokinetic and pharmacodynamic DDIs are predicted based on GAHT, ARV, and DAA pharmacology and adverse event profiles. Clinical management strategies are discussed. Expert opinion: GAHT may be involved in pharmacokinetic and/or pharmacodynamic DDIs. Certain ARV classes (non-nucleoside reverse transcriptase inhibitors, protease inhibitors) may alter GAHT disposition, whereas selected ARVs (unboosted integrase inhibitors, doravirine, or rilpivirine) may have less impact on GAHT. DAAs may interact with GAHT, but the clinical relevance is unclear. ARV- and/or DAA-associated side effects (including depression, cardiovascular disease, hyperlipidemia) are important to consider in the clinical management of trans patients. Clinicians must evaluate potential DDIs and overlapping side effects between ARVs, DAAs and GAHT when providing care for trans patients.